Total postlarvary length of Trichomycterus rivulatus Valenciennes, 1846 (suche) under controlled conditions - Mamani-Ochochoque, Juan (2023)
The objective of the study was to describe the total postlarval length of Trichomycterus rivulatus Valenciennes, 1846 (suche) under controlled conditions. A total of 887 postlarvae of T. rivalatus after 25 days post-hatching was used as biological material. Water quality (temperature, dissolved oxygen and pH) was controlled. Before each feeding, siphoning was done to remove food debris and 90% of the water volume was replaced in all treatments. Growth (total length) was measured with a millimeter ruler (precision ± 0.01) at the beginning and end of the experimental phase. Survival for each experimental treatment before live feed supply was: T2 = 99.66% > T1 = 98.97% > T3 = 97.63%. At 21 days the postlarvae showed an average total length of 21.6 ± 0.51 mm, while at 45 days the total length was 30.53 ± 0.52 mm. A statistical difference was found between the total length at 21 and 45 days: t = -47.80 and p value = 0. The description of the total post-larval length of T. rivalatus under controlled conditions indicated that feeding with Daphnia pulex Linnaeus, 1758 + copepods presented the highest mortality. Choking was observed in the dead individuals. Also, as the number of days increased, there was growth in the postlarvae. It was concluded that the type of live food did not influence the total length of T. rivalatus postlarvae and, after 45 days, growth was significant.